Impact of the Spanish Cooperation program on heritage revaluation in the Historic Center of Lima (1990-2013) - Melgar Montes, Jarim (2019)
In the decade of 1990, Peru lived through a national crisis, a result of the violence in the country and the decrease in the growth of the economy. In this context, the program Heritage for Development of the Spanish Cooperation began its work in the Historic Center of Lima. In a situation in which the priority is not the intervention in cultural assets, a project emerged that seeks to meet society’s different needs through the revaluation of the patrimony. Through this recovery process, there were attempts to instruct people in the craft of restoration, in order to later on include them in the project. The goal of the program at the time was the restoration of heritage and, with the creation of the Escuela Taller de Lima, the project expected to train the population in restoration and conservation work. When the Escuela Taller was introduced as part of the program, it included the social and economic dimension in a bilateral relationship between Peru and Spain, which was mostly cultural in the past.